2009
DOI: 10.1016/j.vetmic.2008.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and correlation with feline infectious peritonitis of feline coronavirus type I and II: A 5-year study in Taiwan

Abstract: The outcomes of feline coronavirus (FCoV) infection vary greatly from asymptomatic or mild enteric infection to fatal feline infectious peritonitis (FIP). On the basis of in vitro neutralization tests, FCoVs can be divided into two serotypes. To explore the correlation between different types of FCoV and FIP, clinical specimens collected from 363 naturally infected cats during 2003-2007 were analyzed. Amplification of a portion of the S gene from the FCoV was performed and a total of 222 cases were differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 26 publications
(49 reference statements)
9
45
0
1
Order By: Relevance
“…Most of the FCoV strains identified in our study belonged to type I FCoV (95.8%, 91/95) according to the phylogenetic analysis of the partial S gene; only four FCoV strains (4.2%, 4/95) were allocated to type II FCoV. In our study, the prevalence of type I FCoV in the FIP‐suspected cats was higher than that of type I FCoV in Taiwan (89.0%, p > 0.05) and Korea (54.5%, p < 0.01) (An et al., ; Lin et al., ). These data suggested that type I FCoV was more prevalent in cats in China.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Most of the FCoV strains identified in our study belonged to type I FCoV (95.8%, 91/95) according to the phylogenetic analysis of the partial S gene; only four FCoV strains (4.2%, 4/95) were allocated to type II FCoV. In our study, the prevalence of type I FCoV in the FIP‐suspected cats was higher than that of type I FCoV in Taiwan (89.0%, p > 0.05) and Korea (54.5%, p < 0.01) (An et al., ; Lin et al., ). These data suggested that type I FCoV was more prevalent in cats in China.…”
Section: Discussionmentioning
confidence: 44%
“…In order to differentiate the type I and type II FCoV strains identified in our study, the partial S gene was amplified by RT‐PCR using the primers described by Lin et al. (). The purified PCR products of the partial S genes were directly subjected to Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Oral infection with non-virulent FCoV serotype I field strains remains clinically inapparent but leads to viraemia FCoV serotype I is known to be the most common serotype in field cases (Hohdatsu et al, 1992;Addie et al, 2003;Benetka et al, 2004;Kummrow et al, 2005;Lin et al, 2009). It differs from serotype II FCoV in that it hardly grows in tissue culture (Jacobse-Geels & Horzinek, 1983); however, oral administration of faeces or gut homogenates from shedding cats leads to intestinal infection and monocyte-associated viraemia (Meli et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the fact that FIP only develops with the occurrence of virulent FCoV mutants, possibly either generated within the individual infected host or acquired externally (Poland et al, 1996;Vennema et al, 1998;Brown et al, 2009;Pedersen et al, 2009;Chang et al, 2010). Two FCoV serotypes, I and II, can be distinguished; these show different geographical prevalence, but, so far, no evident differences in their pathogenic potential (Kummrow et al, 2005;Lin et al, 2009). FCoV is transmitted via the faecal-oral route and primarily infects enterocytes (Pedersen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The current information on the geographical distribution of FCoV indicates a high incidence of Type I in Europe, Japan and USA (Addie et al, 2003;Hohdatsu et al, 1992). However in Japan and Taiwan detection of FIP was associated with Type II FCoV (Hohdatsu et al, 1992;Lin et al, 2009). Presently there is no available information about the molecular epidemiology of FCoV in Portugal.…”
Section: Introductionmentioning
confidence: 99%